Biosynthesis of Hygrocins, Antitumor Naphthoquinone Ansamycins Produced by Streptomyces sp. LZ35. Issue 1 (25th November 2013) - Li, Shanren; Wang, Haoxin; Li, Yaoyao; Deng, Jingjing; Lu, Chunhua; Shen, Yan; Shen, Yuemao
Abstract Hygrocins are naphthoquinone ansamycins with significant antitumor activities. Here, we report the identification and characterization of the hygrocin biosynthetic gene cluster (hgc) in Streptomyces sp. LZ35. A biosynthetic pathway is proposed based on bioinformatics analysis of the hgc genes and intermediates accumulated in selected gene disruption mutants. One of the steps during the biosynthesis of hygrocins is a Baeyer–Villiger oxidation between C5 and C6, catalyzed by luciferase‐like monooxygenase homologue Hgc3. Hgc3 represents the founding member of a previously uncharacterized family of enzymes acting as Baeyer–Villiger monooxygenases.